Investigating the impact of nature-based interventions using mobile low-cost VR on student workload. - Caesaron, Dino; Ardani, Farell (Work, 2026)
Background: Effective workload management in education is crucial for student well-being with nature-based Virtual Reality (VR) interventions presenting a viable solution. Most publications primarily examined high-end VR devices with immersive Head-Mounted Displays (HMDs), leading to a study gap in areas with restricted access to advanced VR technology. Objectives: This study explores the impact of a low-cost non-immersive VR environment on students' workload and cognitive performance in an educational context. Methods: The participants were divided into two groups: a control group using traditional screen-based tasks and an intervention group using low-cost VR tools. Subjective workload was assessed using NASA-TLX and the participants were further categorized based on their perceived workload levels. Objective physiological data, including heart rate variability (HRV) and galvanic skin response (GSR), were recorded, and cognitive performance was measured using the Pauli Test. Results: The results showed no significant differences in physiological, psychological, or performance outcomes between the control and intervention groups, implying that non-immersive VR did not significantly affect stress levels. Due to the limited sensory engagement, non-immersive VR did not activate the body or engage cognition effectively. Conclusion: These findings suggest that the non-immersive VR intervention not sufficient to produce measurable cognitive impact. Future research is encouraged to investigate the potential of immersive VR environments, which might provide a greater sensory experience. In addition, longer exposure durations should be examined to enhance understanding of the effects on cognitive load, relaxation, and overall well-being in nature-based VR applications. Even though differences were not statistically significant, non-immersive VR still reduced stress and enhanced engagement.